Implementasi Pembagian Waris Terhadap Anak Angkat Pada Masyarakat Muslim - Mas’ut; Emy Handayani (Wijayakusuma Law Review, 2025)
Islamic law basically does not prohibit the practice of adopting children, also known as adoption, as long as it does not affect and does not change the relationship between the child and his biological parents. However, Islam prohibits adoption when the adoption will cause problems or problems, namely the severance of the child's relationship with his biological parents. Adoption that is permitted by Islamic law also does not affect inheritance. Islamic law does not make adopted children or adoption a cause of inheritance rights between adopted children and adoptive parents. In Indonesian Muslim society, some of those who do not have children, they adopt children to be their children and it is hoped that when they grow up they can help and support the lives of the adoptive parents. And what is most expected is when the adoptive parents are old, this adopted child is the one who is desired and expected to be able to take care of them later. Adopted children are usually treated like their own biological children in their love. Not a few of these adopted children treat their adoptive parents like their own biological parents in taking care of them when the adoptive parents are old and can no longer do anything. When the adoptive parents have died, of course they leave the property they have as inheritance. And the property left behind will of course be divided among the heirs. While the adopted child who has done such great service to his adoptive parents, of course he will get a share of the property left by his adoptive parents.